Highly thermoconductive yet ultraflexible polymer composites with superior mechanical properties and autonomous self-healing functionality via a binary filler strategy. Issue 2 (9th December 2021) - Wang, Dong; Liu, Dingyao; Xu, JianHua; Fu, JiaJun; Wu, Kai
Abstract : Embedding BNNSs–LM binary fillers into an intrinsic self-healing poly(urea–urethane) elastomer enables the resultant thermally conductive composite to achieve a thermal–mechanical–self-healing balance. Abstract : It is still a formidable challenge to develop ideal thermal dissipation materials with simultaneous high thermal conductivity, excellent mechanical softness and toughness, and spontaneous self-healing. Herein, we report the introduction of sandwich-like boron nitride nanosheets–liquid metal binary fillers into an artificial poly(urea–urethane) elastomer to address the above issue, which confers the composite elastomer with a unique thermal–mechanical–healing combination, including a low modulus, high in-plane thermal conductivity and high mass loading of rigid fillers but self-recoverability and room-temperature self-healing.